Control of heteropolymeric to oligomeric character in electrospray deposited melanin films. Issue 11 (4th August 2016) - Ali, Mushtaq; Shah, Said Karim; Abbas, Mamatimin; Gunnella, Roberto
Abstract: The physicochemical properties of eumelanin thin films realized by spray and electrospray deposition methods were investigated. We find a consistent improvement above the film quality reached from liquid solution, minimizing the detrimental effect of the solvent in the final morphology of the films. Furthermore a clear trend towards specific aggregation modalities made us able to significantly unveil some of the cumbersome physical mechanisms at the basis of the various properties that are often invoked for this important functional biomaterial. In particular, temperature dependent electrical resistance evidenced a semiconductor‐like character, with peculiar features of melanin organization explicated through crosslinked secondary structure as emerged from many observations obtained by different spectroscopic and microscopic techniques. © 2016 Society of Chemical Industry Abstract : A consistent improvement in melanin film quality by electrospray is shown through clearcut characteristics in optical and electronic semiconducting properties.